Microencapsulated Bio-Based Rejuvenators for the Self-Healing of Bituminous Materials - Jose Norambuena-Contreras (Materials, 2020)
Asphalt self-healing by encapsulated rejuvenating agents is considered a revolutionary technology for the autonomic crack-healing of aged asphalt pavements. This paper aims to explore the use of Bio-Oil (BO) obtained from liquefied agricultural biomass waste as a bio-based encapsulated rejuvenating agent for self-healing of bituminous materials. Novel BO capsules were synthesized using two simple dripping methods through dropping funnel and syringe pump devices, where the BO agent was microencapsulated by external ionic gelation in a biopolymer matrix of sodium alginate. Size, surface aspect, and elemental composition of the BO capsules were characterized by optical and scanning electron microscopy and energy-dispersive X-ray spectroscopy. Thermal stability and chemical properties of BO capsules and their components were assessed through thermogravimetric analysis (TGA-DTG) and Fourier-Transform Infrared spectroscopy (FTIR-ATR). The mechanical behavior of the capsules was evaluated by compressive and low-load micro-indentation tests. The self-healing efficiency over time of BO as a rejuvenating agent in cracked bitumen samples was quantified by fluorescence microscopy. Main results showed that the BO capsules presented an adequate morphology for the asphalt self-healing application, with good thermal stability and physical-chemical properties. It was also proven that the BO can diffuse in the bitumen reducing the viscosity and consequently self-healing the open microcracks.